2017
DOI: 10.1111/mec.13969
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity patterns suggesting balancing selection in partially sex‐linked genes of the plant Silene latifolia are not generated by demographic history or gene flow

Abstract: DNA sequence diversity in genes in the partially sex-linked pseudoautosomal region (PAR) of the sex chromosomes of the plant Silene latifolia is higher than expected from within-species diversity of other genes. This could be the footprint of sexually antagonistic (SA) alleles that are maintained by balancing selection in a PAR gene (or genes) and affect polymorphism in linked genome regions. SA selection is predicted to occur during sex chromosome evolution, but it is important to test whether the unexpectedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 66 publications
6
22
0
Order By: Relevance
“…Partial sex-linkage is predicted to lead to more sexually antagonistic alleles 72,77,78 than expected for autosomal regions, but fewer than expected for fully sex-linked regions. Consistent with this prediction, population genetic approaches have shown that there is evidence of increased variation (Tajima's D) for genes on the PAR of Silene latifolia, a dioecious plant 40,41 , which is presumably the result of balancing selection from sexual conflict. Preliminary data from studies of guppies is consistent with the Silene results 54 , suggesting this pattern might be a widespread.…”
Section: Feedback Loops On Sex Chromosomesmentioning
confidence: 83%
See 3 more Smart Citations
“…Partial sex-linkage is predicted to lead to more sexually antagonistic alleles 72,77,78 than expected for autosomal regions, but fewer than expected for fully sex-linked regions. Consistent with this prediction, population genetic approaches have shown that there is evidence of increased variation (Tajima's D) for genes on the PAR of Silene latifolia, a dioecious plant 40,41 , which is presumably the result of balancing selection from sexual conflict. Preliminary data from studies of guppies is consistent with the Silene results 54 , suggesting this pattern might be a widespread.…”
Section: Feedback Loops On Sex Chromosomesmentioning
confidence: 83%
“…Provisional data generated using this method suggests that a substantial proportion of the genome is subject to sexual conflict 29 which may exert a constraint on the evolution of sexual dimorphism. Published studies show that putative sexually antagonistic loci are distributed non-randomly across different genomic regions 40,41 , which is discussed further below.…”
Section: Measuring Balancing Selection From Sequence Diversitymentioning
confidence: 97%
See 2 more Smart Citations
“…These are expected to result in intrinsic genetic isolation fairly early in the speciation continuum, such that secondary contact is unlikely to result in gene flow (Coyne and Orr 2004;Seehausen et al 2014;Nosil et al 2008;Servedio et al 2011;Muir et al 2012;Guirao-Rico et al 2017). Given that hybridisation appears to be the cause of recombination (either in vivo or in vitro) in these Silene individuals, and that the species involved are distinct (Toprak et al 2016), it appears that secondary contact has resulted in some but limited gene flow.…”
Section: Origin Of Recombination Via Introgressive Hybridisationmentioning
confidence: 99%